Make a 2D arcade game in a weekend : with Unity - Sumpter, Jodessiah (Apress, 2015)
Create and complete your first 2D arcade game in Unity. In this book you will learn to create an arcade classic brick breaker game from beginning to end. You will plan the game flow, add the graphics and create the game logic using the C# language, then build the UX to complete your game. By the time you have finished Make a 2D Arcade Game in a Weekend with Unity, you will have enough knowledge to tweak the game to create more levels or your own variant game rules, and you will have the confidence to go on and create your own 2D arcade games. You will also learn how to publish the game into mobile app stores. Unity is a powerful cross platform software tool that allows users to create 2D and 3D apps and games. Learning how to create an arcade classic game is a great way to learn the foundations of game design. While you do need to have a basic understanding of Unity to complete this project, advanced game building or advanced Unity experience is not required. Takes you through building a classic Atari style brick breaker game Provides you the basic knowledge for building games Teaches you how to script and design UI elements of the game.